2019
DOI: 10.1002/pbc.28067
|View full text |Cite
|
Sign up to set email alerts
|

Variation in hospital admission of sickle cell patients from the emergency department using the Pediatric Health Information System

Abstract: Background: Universal newborn screening and improved treatment options have led to increased survival in sickle cell disease (SCD). However, patients with SCD still rely heavily on acute care services. Objective:To determine the variation seen in hospitalizations for the top complaints for ED visits for children with SCD nationally. Methods:We performed a retrospective review of the Pediatric Health Information Systems (PHIS) Database between October 2011 and September 2015. Emergency department (ED) encounter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This admission rate is less than a retrospective review conducted by Jacob et al which reported admission rates ranging from 50% to 60% among SCD patients with VOC. 16 In addition, another retrospective study carried on by Cheng et al) reported an admissions rate of 53%. 17 These findings indicate that a significant proportion of SCD patients presenting with VOC require hospitalization for adequate management and support the results of previous literature in terms of the need for standardized pain management plans, as studied by (Givens et al, Ender et al and Kavanagh et al).…”
Section: Discussionmentioning
confidence: 96%
“…This admission rate is less than a retrospective review conducted by Jacob et al which reported admission rates ranging from 50% to 60% among SCD patients with VOC. 16 In addition, another retrospective study carried on by Cheng et al) reported an admissions rate of 53%. 17 These findings indicate that a significant proportion of SCD patients presenting with VOC require hospitalization for adequate management and support the results of previous literature in terms of the need for standardized pain management plans, as studied by (Givens et al, Ender et al and Kavanagh et al).…”
Section: Discussionmentioning
confidence: 96%
“…In the absence of access to data from a surveillance system such as SCDC, single administrative databases can be useful for identifying trends and health outcomes among subpopulations of people with SCD. [31][32][33][34][35][36] These databases are often straightforward to access and, thus, can rapidly accelerate health services research. Such administrative databases can include discharge data only (eg, Healthcare Cost and Utilization Project, National Inpatient Sample, Pediatric Health Information System) or rely on Medicaid administrative claims (eg, state-specific Medicaid data or Transformed Medical Statistical Information Systems national Medicaid data).…”
Section: Practice Implicationsmentioning
confidence: 99%
“…Adolescence is associated with an increasing frequency of complications in SCD, particularly pain. 13 Children aged 15 to 18 years with SCD make up the largest group of children admitted for pain, 12 and approximately 40% of children aged 16 to 18 years have at least 1 episode of health care utilization for pain over a 1-year period. 13 The period around adolescence is associated with sex differences in pain 21,22 in other painful conditions, but sex differences in acute pain during adolescence are not well described in SCD.…”
Section: Introductionmentioning
confidence: 99%